146 Is there an association between thrombogenesis markers and atrial fibrillation burden in pacemaker population?. (9th June 2011) - Khoo, C W; Krishnamoorthy, S; Dwivedi, G; Balakrishnan, B; Lim, HS; Lip, G Y H
Abstract : Background and Objectives: Contemporary pacemaker devices are able to quantify atrial high-rate episodes (AHREs) and atrial fibrillation burden (AFB) accurately. In this study, we aim to assess the relationship of thrombogenesis markers in association with AHREs and AFB. Methods: We studied 87 patients with dual-chamber pacemaker. Patients on warfarin were excluded. AHREs were defined as atrial-rate ≥220 beats/min and ≥5 minutes. AFB and percentage of cumulative pacing were derived from pacemaker diagnostics. Plasma levels of von Willebrand factor (vWf), tissue factor (TF), soluble P-selectin (P-sel) and D-dimer (DDM) were analysed using ELISA. Results: Baseline characteristics and co-morbidities were comparable between groups (Abstract 146 table 1 ). Patients with AHREs had significantly higher cumulative percentage ventricular pacing (p=0.012). There were no significant differences in levels of vWf, TF, P-sel and DDM between patients with and without AHREs. The AFB ranged from 0 to 99% in AHRE group. TF (r=0.516, p=0.086), P-sel (r=0.795, p<0.001) and DDM (r=0.643, p=0.045) correlated with AFB. On linear regression analysis, both P-sel and DDM were independently associated with AFB (p<0.05). Conclusion: AFB is independently associated with increased indices of P-sel and D-dimer which indicate platelet activation and thrombosis respectively.